Cidades cicláveis: Avanços e desafios das políticas cicloviárias no Brasil - Osmar Coelho Filho; Nilo Luiz Saccaro Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The demand for sustainable mobility in Brazil is driven by the Brazilian cities growing urban density, the increased travel time in different transportation modes, the increasing number of motorcyclists deaths who migrated from active modes driven by household income growth as well as drivers, pedestrians and cyclists deaths, and the worsening air pollution level linked to combustion engines which has serious consequences for health. Brazil has more bikes than cars, respectively 50 million to 41 million. Around 7% of all trips are made by bicycle with a potential to reach 40%. This qualitative research tried to understand what are the cycling networks future scenarios and sustainability factors that can guide the empowering of cycling policies and the sustainable mobility in Brazil. It used the pressure-state-response methodology associated with life cycle thinking methodology (PCV) to understand the cycling networks stakeholder perceptions from academia, government, cycling associations and business associations. Short-term scenarios indicated a database construction to support the development of social, economic and environmental indicators, and the empowering of the social actors' participation in the cycling policy institutionalization. Medium-term scenarios indicated the construction of strategic alliances among stakeholders and the strengthening of bicycle culture or "bike wave" through events and production of information to social actors in different territory scales (local, national and international). The sustainability factors to empower cycling policies were: the policy implementation timing; the mobility approach strand used to guide the cycling policy; the levels of economic and tax incentives; the participatory methodologies use; the database on number and location conflicts among drivers, pedestrians and cyclists; the level of cycling policy integration with other public policies; and the urban space available area for the expansion of cycling networks. Moreover, the Life Cycle Thinking methodology indicated the development of a life cycle assessment (LCA) that models the impacts on each transportation mode and its available urban space (pedestrian, bicycle, subway, train, and bus). This LCA can produce indicators that support an integrated sustainable mobility where the bicycle may have multiple roles: transportation mode, integration vehicle among modes and sustainability symbol.
Keywords: R40; 330; mobility; sustainable; urban; bike; bicycle path